Critical Analysis of Cryptographic Algorithms - AlRoubiei, Mazoon; AlYarubi, Thuraiya; Kumar, Basant (2020 8th International Symposium on Digital Forensics and Security (ISDFS), 2020)
Security is the most important role in data communication due to the increase of the intruder's possibility of alteration and eavesdropping to the sensitive data. Hence, cryptography is the fundamental tool used to protect these data. The purpose of using cryptography is to achieve privacy via preventing disclosure of the communication where the data are converted from a readable form into an unreadable form and vice versa. The cryptography algorithm has two types namely: Symmetric key and Asymmetric key. Asymmetric key algorithm mainly invented to overcome the dilemma of key distribution in symmetric key. There are several algorithms classified under these two types based on different parameters. Hence, this variation leads to different levels of performance and efficiency of these algorithms. This paper presents a critical analysis of these systems based on a detailed study and literature review of some cryptography algorithms.